A nonlinear adaptive fuzzy controller with signal transmission delay compensation for steel rope tension active control of mining hoists. (August 2022) - Li, Xiang; Zhu, Zhen-Cai; Shen, Gang; Tang, Yu
The double-rope winding hoists have been widely used in the ultra-deep mines. However, there exists tension imbalance issue on two steel rope of the double-rope winding hoist. The passive tension control method is not ideal in both adjust accuracy and response speed. Therefore, a novel hybrid control method is proposed for active control of two steel rope tensions considering the wireless transmission delay of steel rope tension signal, nonlinear uncertainties, and external disturbance. First, a signal transmission delay compensator is designed to obtain the observed feedback signal and other correlated variables. It is worth mentioning that the effectiveness of designed signal transmission delay compensator is verified not only in theory and simulation but also by experiments. Then, a hybrid controller that combines the adaptive backstepping theory and adaptive fuzzy algorithm is designed to obtain the active control output of two steel rope tensions. It is theoretically depicted that the proposed nonlinear adaptive fuzzy controller combined with the signal transmission delay compensator not only achieves good robust performance on model uncertainty but also improves the closed-loop system response rate. Moreover, the proposed controller can compensate external disturbance and suppress chattering caused by ordinary methods based on backstepping technology. The stability of the integrated closed-loop system with the hybrid controller is proved on the basis of Lyapunov theory. In order to demonstrate the feasibility and effectiveness of the proposed nonlinear adaptive fuzzy controller combined with the signal transmission delay compensator, a double-rope winding hoisting simulated test device is set up for experimental investigation. Then, contrast experiments with the traditional proportion–integration, adaptive backstepping controller, and the proposed controller are conducted on the test device. Experimental results verify the superior of the proposed nonlinear adaptive fuzzy controller combined with the signal transmission delay compensator on tension control of two steel ropes for the double-rope winding hoist.